Perancangan Sistem Informasi Helpdesk Menggunakan Website Design Methode Dalam Mendukung Tata Kelola Teknologi Informasi - Pamnungkas, R Wisnu Prio; Alexander, Allan D; Reza, Ali (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Information Technology is important in increasing efficiency and efficiency in achieving company goals. Is a regionally owned company that in carrying out the functions and duties of clean water services for customer needs is never separated from the company's services to customers. Thus the helpdesk application is designed as a Single Point of Contact to focus on customer service issues. The purpose of this research is to analyze and manage the helpdesk application with a display design using the website design method. Built with PHP and MySql database, the application aims at implementing ITIL, which is useful for managing and assisting any problems (reporting) and service requests (requirements) to be sent to the unit that manages the handling schedule based on priority weights.